Silver(I) complex with 2-amino-4, 4α-dihydro-4α, 7-dimethyl-3H-phenoxazin-3-one (Phx-1) ligand: crystal structure, vibrational spectra and biological studies. Issue 20 (18th October 2017) - Helios, K.; Maniak, H.; Sowa, M.; Zierkiewicz, W.; Wąsińska-Kałwa, M.; Giurg, M.; Drożdżewski, P.; Trusek-Hołownia, A.; Malik, M.; Krauze, K.
Abstract: The first metal complex of Phx-1 ligand, bis(2-amino-4, 4α-dihydro-4α, 7-dimethyl-3 H -phenoxazin-3-one)nitratosilver(I), [Ag(Phx-1)2 NO3 ], has been obtained and investigated by single crystal X-ray diffraction and vibrational spectroscopy methods. The Ag + is bonded to heterocyclic nitrogen atoms of two organic ligands and one oxygen atom of a nitrate anion. The Phx-1 ligand coordination mode is supported by IR and Raman spectra, interpreted with the help of theoretical DFT studies. The antibacterial activity of the ligand and its Ag(I) complex as well as some reference compounds were screened against Gram-positive and Gram-negative bacteria, applying microdilution procedures. High sensitivity to the studied complex was found for Rhodococcus erythropolis and Bacillus licheniformis strains. Modified Phx-1 ligand preparation procedures are also presented. Abstract :